Internet of Things Based on Arduino Heart Rate Health Care Monitor System - Inbavalli, M; Prameela, N (International Journal of Computer Sciences and Engineering, 2025)
Health care monitoring system is used to patients body temperature and heartbeat by using health care technique. The doctors to test the patients health conditions .In the world spread many diseases for the patients to spread some disease are cancer ,heart attack ,etc… , Many of people are death affecting families, communities and countries. Health care system is organization of the people institution and deliver health care services to meet the health needs of population .The doctor monitoring the system is provided by using delivery machine, blood pressure monitor ,heartbeat sensor .This system is to detect the abnormal conditions . The patient’s heart beat count the abnormal times to check the pulse using sensor monitoring .To circulate the blood in body in active mode or passive mode of the body temperature .In this paper introduce the IOT based health care monitoring system.